Beyond behavioral change: evaluating the impact of environmental films on audience perceptions and beliefs about food system issues - Majestya, Nayla; Irwanto, Irwanto (Frontiers in Communication, 2025)
This study examines the effects of environmental films on audience beliefs and perceptions regarding food system issues. Specifically, it evaluates the impact of viewing documentary Food, Inc. and fictional film Okja on undergraduate film students. Using a Stimulus-Organism-Response framework, the researchers conducted pre-and post-questionnaires to measure participant motivations, beliefs, and perceptions. Statistical analysis using paired-sample t-tests revealed no significant differences in belief evaluations before and after viewing either film. However, both films observed substantial changes in perception assessments, with Okja demonstrating a stronger effect than Food, Inc. The study found that while both films increased audience knowledge about food systems and sustainability issues, they did not significantly alter food consumption habits. Instead, the films functioned as moral fables, providing a foundation for environmental ethics rather than directly influencing behavior. Food, Inc. primarily addressed instrumental-value ecological ethics, focusing on human health and business practices, while Okja emphasized intrinsic-value ethics, particularly animal rights. The research challenges the notion that environmental films’ primary purpose is to change audience behavior directly, arguing instead that they serve as a form of ecological communication with distinct moral and political agendas. The study concludes that these films engage in moral pedagogy to promote environmental ethics by narrating injustices in the existing food system, ultimately aiming to influence social change through policies rather than individual actions. This research contributes to understanding the nuanced effects of environmental films on audience perceptions and beliefs, highlighting the importance of considering both media logic and media effects in analyzing their impact.